2012
DOI: 10.1007/s00592-012-0377-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting educational therapy for type 2 diabetes: identification of predictors of therapeutic success

Abstract: Patient education is a key component of diabetes care. Limits in resources often prevent the participation of many patients with type 2 diabetes to structured education programs. The identification of predictors of response to group education could help in selecting those patients in whom the intervention is more cost-effective. A structured interactive group program was proposed to a consecutive series of 150 type 2 diabetes patients, who were then followed prospectively in 24 months, with measurements of HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Since, we measured the change in HbA1c only after 3 months of the enrollment and during the initial 1 month, 4 weekly sessions were conducted thus the time to bring change in the daily routines, behaviors, practices based on the education resulting in improvement of HbA1c might not be sufficient. Secondly, studies in the past have reported that improvement in the HbA1c level is relatively difficult among diabetes patients with longer duration of the illness as compared to the patients who are newly diagnosed [33]. Since the average of duration of illness in this study was 10 and 9 years among patients in the DCM and RC arms respectively, therefore, longer duration might have resulted in no significant improvement in HbA1c during the 3 months duration after enrollment.…”
Section: Discussionmentioning
confidence: 72%
“…Since, we measured the change in HbA1c only after 3 months of the enrollment and during the initial 1 month, 4 weekly sessions were conducted thus the time to bring change in the daily routines, behaviors, practices based on the education resulting in improvement of HbA1c might not be sufficient. Secondly, studies in the past have reported that improvement in the HbA1c level is relatively difficult among diabetes patients with longer duration of the illness as compared to the patients who are newly diagnosed [33]. Since the average of duration of illness in this study was 10 and 9 years among patients in the DCM and RC arms respectively, therefore, longer duration might have resulted in no significant improvement in HbA1c during the 3 months duration after enrollment.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, in the Da Vico study, where the proportion of poor diabetes mellitus control was 36.7% at 12 months after the diagnostic of diabetes mellitus, all patients had received therapeutic education [34]. Our high proportion of poor diabetes mellitus control could be explained by the low completion rate of therapeutic education in the patient population, 24.3% [35] versus 100% [34]. Indeed, therapeutics education creates conditions for improved patient compliance and follow-up.…”
Section: Prevalence Of Prolonged Poor Control Of Diabetes Mellitusmentioning
confidence: 75%
“…Distribution of study patients by diabetes mellitus characteristics (N = 270).In multivariate analysis with bivariate logistic regression, six factors were independently associated with prolonged poor diabetes mellitus control. These were no formal education (OR = 8 34,. 95% CI [1.97 -35.22]; p < 0.01); family support for diabetes mellitus management (OR = 0.65, 95% CI [0.45 -0.94]; p = 0.02); presence of abdominal obesity (OR = 2.27, 95% CI [1.08 -4.77]; p = 0.03); a history of hospitalization (OR = 7.39, 95% CI [2.97 -18.39]; p < 0.01); poor adherence to antidiabetic treatment (OR = 2.97, 95% CI [1.42 -6.18]; p < 0.01); presence of microangiopathy (OR = 5.05, 95% CI [2.36 -10.81]; p < 0.01).…”
mentioning
confidence: 99%
“…As expected, patients with higher BMI had greater problems with snacking between main meals than patients with normal weight. This finding may have clinical implications because higher basal BMI is a negative predictor of success in diabetes treatment,19 and obesity is associated with worsened glycemic control in patients with T2DM treated with insulin 20…”
Section: Discussionmentioning
confidence: 99%